Dimensi Sosial dalam Novel "Selembar itu Berarti" karya Suryaman Amipriono - Lestari, Dina; Shomary, Sudirman (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2024)
This study discusses social values ​​in the novel Selembar Itu Means by Suryaman Amipriono. The social values ​​that will be examined are social interaction, social change, and social problems. This study uses a qualitative approach with a descriptive method that describes an actual situation. The data analysis used is content analysis. Social value in the novel Selembar Itu Means by Suryaman Amipriyono. Researchers discuss social values ​​in the novel Selembar Itu Means by Suryaman Amipriyono. Aspects listed in social values ​​are, social interaction, social change and social problems. Of the three, what is more dominant in the novel is the discussion of social interaction. Based on the analysis of the data that the researcher found, the researcher can conclude that the author mostly describes the relationship between people, individuals, between groups of people and between individuals and groups of people. The reason is because in the novel Selembar Itu Means by Suryaman Amipriyono it tells a lot about dynamic social relations that involve relations between individuals, between groups of people, as well as between individuals and groups of people.